GENEALOGI PEMIKIRAN ANGELIKA NEUWIRTH TENTANG TARTIB NUZULI SEBAGAI METODE PENAFSIRAN AL-QUR’AN - Asyrifah Luthfiana Azmi; Nurun Nisaa Baihaqi; Aidah Mega Kumalasari (Al'Adalah, 2022)
Tartib nuzuli (understanding the Qur’an considering arrangement drop of exposure) is one of the strategies for translating the Qur’an that researchers seldom discuss). Among the researchers who focused on the idea was Angelika Neuwirth. Tartib nuzuli initiated by Neuwirth can add to the investigation of the Qur'an. The review utilized a subjective exploration of the ancestry hypothesis to show up at Neuwirth's reasoning. The results showed that Neuwirth emphasized the need for hermeneutic devices to bring the Post-canonized Qur'an to life based on its chronology. With a literary and historical approach, the Qur'an is analyzed in synchronic and synchronized through time frames (beginning with pre- canonization in the Meccan phase). Furthermore, the Qur'an is analyzed with units of letters and intertextuality. Neuwirth's marginalized opinion was his critique of the study of scholars who focused on post-codification texts rather than uncovering his pre-canonized side. Despite the attention to the aspect of canonization, some Western scholars still produce sensitive arguments, as well as Muslim scholars who do not necessarily make Tartib nuzuli a method of Qur'anic interpretation. Among the factors of Neuwirth's thought: Firstly, his early interest in the Qur'an, literature, and history. Secondly, he was affected by his educators, for example, Anthonie, to reinforce his advantage in investigating the Qur’an. Thirdly, they are affected by the considerations of prior figures who are also consensual in the idea of the Qur’an order. Among the ramifications of Neuwirth's reasoning: 1) present a variety of strategies for translation; 2) open a more open and logical exchange; 3) it is the center ground of concepts in the Qur’an; and 4) the Corpus Coranicum was shaped like an actual demonstration of his reasoning.